TWO NEW FORMS OF QUASI-H-CLOSEDNESS VIA IDEALS - Pachon Rubiano, Néstor Raúl (Publicaciones académicas Ltd., 2017)
In this paper we introduce two new ideal topological spaces, which are strong forms of the QHC spaces and the I -QHC spaces. We present several properties and characterizatios of these new spaces.

En este trabajo introducimos dos nuevos espacios topológicos ideales, que son formas fuertes formas fuertes de los espacios QHC y los espacios I -QHC. Presentamos varias propiedades y caracterizaciones de estos nuevos espacios.
Keywords: Matemáticas; Acciones de grupos (Matemáticas); C-compact; quasi-H-closed; I-compact, C(I); compact; I-QHC; I-compact; C(I)-compact; I-compact; C-compacto; cuasi-H-cerrado; I-compacto, C(I); I-QHC; compacto; I-compacto; I-QHC; C(I)-compacto; I-QHC; I-compacto